2015
DOI: 10.1002/jmv.24216
|View full text |Cite
|
Sign up to set email alerts
|

Detection prevalence of H5N1 avian influenza virus among stray cats in eastern China

Abstract: Since 1997, more and more cases of the infectious H5N1 avian influenza virus (AIV) in humans have been reported all over the world but the transmission of H5N1 avian influenza virus to stray cats has been little demonstrated. The objective of this pilot investigation was to determine the prevalence of H5N1 AIV antibodies in stray cats in eastern China where is the dominant enzootic H5N1 highly pathogenic avian influenza virus (HP AIV). A total of 1,020 nasal swab and 1,020 serum samples were collected and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Isolation of H5N1 and H5N6 viruses from cats, leopards, lions, and tigers and subsequent experimental inoculation of these and related species illustrate the capacity for avian influenza viruses to cause severe disease and death in domesticated, wild, or captive felids (37-41). However, while serological studies suggest that avian influenza viruses do not appear to be widely prevalent in cats (42,43), they have detected a relatively elevated seroprevalence of seasonal H1N1, H3N2, and, especially, 2009 pandemic H1N1 viruses in domestic felids (44)(45)(46). Confirmed influenza virus infection of domestic cats has occasionally resulted in fatal infection in these animals, most frequently documented with 2009 H1N1 viruses, and it is believed that human-to-cat virus transmission is responsible in at least some of these cases (10)(11)(12)47).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of H5N1 and H5N6 viruses from cats, leopards, lions, and tigers and subsequent experimental inoculation of these and related species illustrate the capacity for avian influenza viruses to cause severe disease and death in domesticated, wild, or captive felids (37-41). However, while serological studies suggest that avian influenza viruses do not appear to be widely prevalent in cats (42,43), they have detected a relatively elevated seroprevalence of seasonal H1N1, H3N2, and, especially, 2009 pandemic H1N1 viruses in domestic felids (44)(45)(46). Confirmed influenza virus infection of domestic cats has occasionally resulted in fatal infection in these animals, most frequently documented with 2009 H1N1 viruses, and it is believed that human-to-cat virus transmission is responsible in at least some of these cases (10)(11)(12)47).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, these were connected to infected wild birds or poultry. Nevertheless, even in areas in which birds are infected with H5N1 IAV, cats are rarely positive by serology or PCR [ 56 , 57 ]. Experimental infections have confirmed that the highly pathogenic H5N1 IAV may induce a severe, fatal disease in domestic cats, and can spread via cat-to-cat contact [ 23 , 24 , 58 ].…”
Section: Epidemiology Of Iav Infections In Catsmentioning
confidence: 99%
“…Subclinical infection of cats with H5N1 was also reported after contact with infected birds or their excrement (22), thus indicating that cats may serve as a potential asymptomatic H5N1 reservoir. Nevertheless, low prevalence of H5N1 antibodies was reported in cats sera, even in areas in which birds infected with HPAIV H5N1 had been documented (23,57,58).…”
Section: Epidemiology Of Iav In Cats and Dogsmentioning
confidence: 98%